2015
DOI: 10.1007/s10899-015-9531-4
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Mistaken Identity? A Comparison of Professional and Amateur Problem Gamblers

Abstract: Professional gamblers are more likely than amateur gamblers to meet criteria for problem gambling but minimal research has examined their gambling behavior and its consequences. This study compared gambling behavior, problem gambling symptoms, related harms, recognition, and help-seeking among problem semi/professional gamblers (PPGs/PSPGs) and problem amateur gamblers (PAGs). Surveys completed by 57 self-identified professional gamblers, 311 semi-professional gamblers and 4226 amateur gamblers were analysed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…From a problem gambling perspective, future research should focus on esport players' psychological vulnerability, as some studies have begun to investigate the difference between problematic and professional gambling (Hing et al 2016;Weinstock et al 2013). According to research focused on the different ways of gambling on the same activity,…”
Section: Discussionmentioning
confidence: 99%
“…From a problem gambling perspective, future research should focus on esport players' psychological vulnerability, as some studies have begun to investigate the difference between problematic and professional gambling (Hing et al 2016;Weinstock et al 2013). According to research focused on the different ways of gambling on the same activity,…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found high rates of problem gambling amongst self-nominated professional gamblers, raising queries over whether self-identifying as a professional gambler is a common but misguided way to rationalize problem gambling (Hing et al, 2015a, 2016b). Browne et al (2015) argue that race betters are prone to suffer from ‘delusions of expertise,’ due to intrinsic difficulties in self-assessing skill based on betting returns.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there are concerns regarding gambling in the workplace [56,57]. Otherwise, the red group could represent professional players, gambling on working or night hours [58,59]. …”
Section: Discussionmentioning
confidence: 99%